PELUANG DAN TANTANGAN PEMERINTAH PROVINSI JAWA BARAT DALAM MENDORONG REVOLUSI INDUSTRI 4.0 DI SEKTOR INDUSTRI - Idris, Syaharuddin (Badan Penelitian dan Pengembangan Daerah (BP2D) Provinsi Jawa Barat, 2020)
This research aimed to investigtate the Government of West Java’s opportunities and challenges headed to support the implementation of the Fourth Industrial Revolution, especially in manufacture. The study utilized qualitative approach and framed by External Factors Analysis to expose its results to three points, opportunities, challenges, and recommendation of policy alternatives in responding the trend of Industrial Revolution 4.0 in West Java. The investigation found three opportunities concerning the issue i.e. the government commitment to encourage the development of industrial sector; supporting infrastructure of manufacture; and the government cooperation networks to enrich inputs and ideas about the development of manufacture. On the other hand, three challenges were identified in aspects of worker issues; environmental issues; and bureacreatical problems. Therefore, some alternatives recommended to be implemented to address the government of West Java’s effort to encourage the implemetation of the Fourth Revolution concepts in West Java’s industry were encourage research, development, and training; diversify product of manufacture; and promote export activities.